GE_GERICHTE C/7105/2017 vom 16. April 2019 - GE Cour de justice (2019)
DIVORCE;AUTORITÉ PARENTALE;OBLIGATION D'ENTRETIEN;ENFANT;MAJORITÉ(ÂGE);PRÉVOYANCE PROFESSIONNELLE;CONTRIBUTION EXTRAORDINAIRE D'UN ÉPOUX | CC.296; CC.265; CC.165; CC.277